2018
DOI: 10.11648/j.aff.20180702.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spacing on Yield Components and Yield of Chickpea (<i>Cicer arietinumL. </i>) at Assosa, Western Ethiopia

Abstract: A field experiment was conducted in Assosa District of western Ethiopia during 2013 cropping season to determine the effect of different inter row (20, 30, 40, 50cm) and intra row spacing (5, 10, 15cm) on growth parameters, yield components and yield of Desi chickpea. The experimental design was randomized complete block design in factorial arrangement with three replications. There was highly significant (P<0.01) effect of both inter row and intra row spacing on days to 50% flowering, days to 90% maturity, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
5
4
0
Order By: Relevance
“…Recently, Shiferaw et al (2018) reported that chickpea cultivars planted at higher densities (10 cm × 20 cm between plants and rows spacing) gave the highest grain yield. Coupled with this result, Agajie (2018) reported that 10 cm × 30 cm spacing resulted in the highest grain yield, which also confirmed the earlier recommendation (Eshete 1994). These and many other studies reported that chickpea plant better tolerate higher plant population culture.…”
Section: Planting Densitysupporting
confidence: 90%
“…Recently, Shiferaw et al (2018) reported that chickpea cultivars planted at higher densities (10 cm × 20 cm between plants and rows spacing) gave the highest grain yield. Coupled with this result, Agajie (2018) reported that 10 cm × 30 cm spacing resulted in the highest grain yield, which also confirmed the earlier recommendation (Eshete 1994). These and many other studies reported that chickpea plant better tolerate higher plant population culture.…”
Section: Planting Densitysupporting
confidence: 90%
“…The lack of environmental influence on 1000 seed weight could be attributed to the absence of significant influence of plant spacing on 1000 seed weight. This finding observed in the study is in agreement with [31] in the study of the effect of spacing on yield of chickpea. The interactive effect between Asomdwe at 45 x 15 cm and Videza at 60 x 15 cm for 1000 seed weight shows the genotype and environment influence on 1000 seed weight.…”
Section: Seed Weight Grain Yield and Fodder Yieldsupporting
confidence: 93%
“…Similarly, [160] observed that plant and row spacing improve WUE and yield components in soybean. Agajie et al [161] studied the effect of spacing on yield components and yield of chickpea. They described that proper row spacing is critical for growth, yield components, and yield of chickpea.…”
Section: Management Strategiesmentioning
confidence: 99%